2022
DOI: 10.3389/fnut.2022.867926
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Bangladeshi Adults’ Demographics, Personal Beliefs, and Nutrition Literacy: Evidence From a Cross-Sectional Survey

Abstract: BackgroundPoverty and health illiteracy, combined with inappropriate systems to track disease and infection rates, contribute to children-and-mothers’ poor adherence to nutrient-rich foods intake in Bangladesh. Although risk factors for child and pregnant women malnutrition have been explored, the relationship between Bangladeshi adults’ nutrition literacy and their demographics and personal beliefs remains unknown. The purpose of this study was to examine the association between adults’ nutrition literacy, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In this study, the total score of FNLI in females was found to be significantly higher than in males (Table 2). It is possible to find similar results in studies in the literature [42,43]. Having high nutritional knowledge is very important for public health.…”
Section: Discussionmentioning
confidence: 56%
“…In this study, the total score of FNLI in females was found to be significantly higher than in males (Table 2). It is possible to find similar results in studies in the literature [42,43]. Having high nutritional knowledge is very important for public health.…”
Section: Discussionmentioning
confidence: 56%
“…Previous research showed that nutrition literacy can be influenced by different factors. For example, Banna and colleagues [ 19 ] reported Bangladeshi adults’ nutrition literacy was associated with sociodemographic factors, such as residence, occupation, education level, family income, and personal beliefs (e.g., self-perceived need for access to nutrition-related information). Findings of the present research highlight the need to improve adults’ nutrition literacy by addressing demographic factors, which might impact positively attitudes, and subsequently improve healthy eating behaviors in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported a moderate level of nutrition literacy among Bangladeshi adults and evidence that socio-demographic factors were associated with nutrition literacy [ 19 ]. In Bangladesh, understanding how food choice is associated with an individual’s nutrition literacy and sociodemographic factors would be useful to effectively implement National Dietary Guidelines (2015), National Nutrition Policies (2015), and the Second National Plan of Action for Nutrition (2016–2025) and achieve nutrition targets [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, the following features were considered: (i) since there is no any comparable research on food neophobia in Bangladesh, a 50% predicted prevalence was chosen (p = 0.5). Likewise, 50% was taken as the anticipated prevalence in several previous studies [ [36] , [37] , [38] , [39] , [40] ]. (ii) 95% level of confidence (Z = 1.96) and (iii) 5% margin of error (d = 0.05).…”
Section: Methodsmentioning
confidence: 99%